GM1 ganglioside reverses the cognitive deficits induced by MK801 in mice. Issue 5 (August 2016) - Ni, Yu-Fei; Zhang, Wei; Bao, Xiao-Feng; Wang, Wei; Song, Lu; Jiang, Bo
Abstract : Cognitive deficits are core symptoms of schizophrenia, but effective treatments are still lacking. Previous studies have reported that the brain-derived neurotrophic factor (BDNF) signaling is closely involved in learning and memory. Monosialotetrahexosylganglioside (GM1) is a ganglioside with wide-ranging pharmacologic effects that enhances the BDNF signaling cascade. This study aimed to assess the effects of GM1 on schizophrenia-related cognitive impairments. A brief disruption of N -methyl-D-aspartate receptors with MK801 was used to generate the animal model for cognitive deficits in schizophrenia. It was found that MK801-treated mice showed significant deficits in memory ability compared with control mice in different behavior tests, and this was accompanied by decreased hippocampal BDNF signaling pathway. Consecutive administration of GM1 fully restored the MK801-induced cognitive deficits and the impaired BDNF signaling in the hippocampus. Furthermore, a BDNF system inhibitor abolished the effects of GM1 in the MK801 model. Taken together, our results show that GM1 could reverse the MK801-induced cognitive deficits, suggesting a potential usefulness of GM1 in treating the schizophrenia-related cognitive impairments.